Cerebral and cerebellar language organization in a right-handed subject with a left temporal porencephalic cyst: An fMRI study. (February 2016) - De Coninck, Mattias; Van Hecke, Wim; Crols, Roel; van Dun, Kim; Van Dam, Debby; De Deyn, Peter P.; Brysbaert, Marc; Mariën, Peter
Abstract: To test the hypothesis of crossed cerebro-cerebellar language dominance (Mariën, Engelborghs, Fabbro, & De Deyn, 2001) in atypical populations, the pattern of cerebral and cerebellar language organization in a right-handed woman with a large porencephalic cyst in the left temporal lobe with no secondary clinical neurological symptoms was studied by means of an fMRI-language paradigm. Extensive neuropsychological examinations were performed to formally rule out cognitive dysfunctions. The fMRI task, consisting of a covert controlled oral word generation task, disclosed a pattern of bilateral activity in the frontal language areas, slightly more pronounced in the left hemisphere, and unilateral activation of the left inferior and superior temporal and supramarginal gyrus. This pattern of supratentorial activations was reflected at the infratentorial level by bilateral activations in the posterior lobe of the cerebellum with slightly more activity located in the right cerebellar hemisphere. This pattern of bilateral cerebral and cerebellar activation seems to confirm that the distribution of supratentorial language dominance is intrinsically reflected at the level of the cerebellum. Bilateral frontal language representation might be the consequence of neurofunctional compensation for the structural anomaly affecting eloquent brain regions resulting in an operational inefficiency of the neural network subserving language in the left hemisphere. Highlights: Bilateral language organization was observed in a subject with porencephaly. Secondary clinical neurological, neurodevelopmental and clinically significant neurocognitive deficits were excluded. Pattern of bilateral frontal activity was reflected at the cerebellar level. Lateralization indices confirmed the atypical language organization. Bilateral frontal language function is a compensatory mechanism for the cyst.